A Pediatric Case of Disseminated Lichen Sclerosus – a Case Report - Gocev, Gjorgji; Nikolovska, Suzana; Dohcheva Karajovanov, Ivana (Walter de Gruyter GmbH, 2017)
Lichen sclerosus (LS) is an uncommon chronic inflammatory skin disorder with a predilection for the anogenital area, characterized by porcelain white papules, plaques and atrophic patches. We report a prepubertal, 12-year-old girl who presented with chronic, disseminated pearly, flat-topped papules, plaques and atrophic patches located on the trunk, limbs and in the anogenital area, consistent with LS based on clinical and histologic findings. Potent and ultrapotent topical corticosteroids should be considered as first-line treatment. The ultraviolet A1 (UVA1) and calcipotriol for extragenital lesions, as well as calcineurin inhibitors for anogenital lesions, are other treatment options for pediatric LS.
Keywords: Lichen Sclerosus et Atrophicus; Vulvar Lichen Sclerosus; Child; Diagnosis; Clobetasol; Skin Dis-eases; Treatment Outcome; Signs and Symptoms